2018
DOI: 10.1109/tccn.2018.2881442
|View full text |Cite
|
Sign up to set email alerts
|

A Very Brief Introduction to Machine Learning With Applications to Communication Systems

Abstract: Given the unprecedented availability of data and computing resources, there is widespread renewed interest in applying data-driven machine learning methods to problems for which the development of conventional engineering solutions is challenged by modelling or algorithmic deficiencies. This tutorial-style paper starts by addressing the questions of why and when such techniques can be useful. It then provides a high-level introduction to the basics of supervised and unsupervised learning. For both supervised a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
295
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 449 publications
(302 citation statements)
references
References 82 publications
0
295
0
7
Order By: Relevance
“…In order to enable reinforcement learning, a loss metric is measured at the receiver and communicated over a reliable channel to the transmitter. A detailed review of the state of the art can be found in [9] (see also [10] for recent work).…”
Section: Introductionmentioning
confidence: 99%
“…In order to enable reinforcement learning, a loss metric is measured at the receiver and communicated over a reliable channel to the transmitter. A detailed review of the state of the art can be found in [9] (see also [10] for recent work).…”
Section: Introductionmentioning
confidence: 99%
“…T applies a deep learning classifier C T to identify Algorithm 2 T 's training algorithm 1: T collects sensing data over a time period to build its training data D train . 2: T builds a training sample {F t , S t } for each time t ≥ n new , where F t = (p t−nnew−1 , p t−nnew−2 , · · · , p t ), p t is the sensed power at time t, and S t is the busy/idle status at time t. 3 idle time slots. C T is pre-trained using a number of samples, where a sample for time t has the most recent n new sensing results p t−nnew−1 , p t−nnew−2 , · · · , p t as features F t and the current busy/idle status S t as the label.…”
Section: Transmitter's Algorithmmentioning
confidence: 99%
“…As discussed in Sec. I, we view demodulation as a classification task (see, e.g., [1], [2]). Accordingly, given set D T , a demodulator p θ (s|y) can be trained by minimizing the crossentropy loss function:…”
Section: Meta-learning Algorithmmentioning
confidence: 99%
“…We now consider a more realistic scenario including Rayleigh fading channels h k ∼ CN (0, 1) and an amplifier's distortion given by (2), where α k = 4 and β k is uniformly distributed in the interval [0.05, 0.15]. We assume 16-ary quadrature amplitude modulation (16-QAM) S and the sequence of pilot symbols in the meta-training dataset D and meta-test dataset D T was fixed by cycling through the symbols in S, while the transmitted symbols in the test set for the metatest device are randomly selected from S. The number of metatraining devices is K = 20; the number of pilot symbols per device is N = 32, which we divide into N tr = 16 metatraining samples and N te = 16 meta-testing samples.…”
Section: B a More Realistic Scenariomentioning
confidence: 99%
See 1 more Smart Citation